Three new species of liocranid spiders (Arachnida: Araneae) from China and Nepal - Chu, Chang; Lu, Ying; Li, Shuqiang; Yao, Zhiyuan (Zootaxa, 2023)
Three new species of spiders belonging to the genera Oedignatha Thorell, 1881 and Paratus Simon, 1898 of the family Liocranidae Simon, 1897 are described from China and Nepal: Oedignatha shaanxi sp. nov. (female only; Shaanxi, China), Paratus bagmati sp. nov. (male only; Bagmati, Nepal), and P. ledong sp. nov. (both sexes; Hainan, China). In addition, Liocranidae is reported from Nepal for the first time.